Quality of Institutions and Total Factor Productivity in European Union - Adam P. Balcerzak; Michal Bernard Pietrzak (Institute of Economic Research (IER), 2015)
The key challenge for medium- and long-term policy in European Union countries is to use the potential of knowledge-based economy (KBE), which is a condition for maintaining high total factor productivity in Europe. For this reason, the relationship between quality of institutional system and total factor productivity in the EU countries has been examined. The quality of institutional system is defined here from the perspective of incentives that influence the use of the potential of KBE. In order to determine the level of effectiveness of the institutional system in the analyzed countries the method for linear ordering of objects was applied based on data from Fraser Institute. The main hypothesis of the article was formed as follow: the quality of institutional system in the context of KBE has significant influence on the level of total factor productivity in the EU. In order to verify the hypothesis, the parameters of the Cobb-Douglas production function were estimated, which allowed to evaluate TFP for EU countries. The calculation made in the article was based on Eurostat data. Then, the identification of the relationship between the quality of institutional system and the level of TFP was made with the application of panel model. The research made for the years 2000-2010 allowed to verify the hypothesis.
Keywords: D24; E02; 330; Knowledge-based economy; TFP; quality of intuitions; European Union; panel model